The Influence of Perceived Organizational Support on Subjective Career Success with Career Adaptability as a Mediating Variable on Employees of The Finance Department and Human Resources Department of PT. Semen Padang - Taufik Hidayat; Yuki Fitria (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The significance of organizational support in influencing employees' subjective career success and the potential for career adaptability to reinforce this relationship form the foundation of this study. The Partial Least Square–Structural Equation Modeling (PLS-SEM) methodology, which is based on the grand theory of work Construction Theory (CCT), is a quantitative research method that highlights the significance of an individual's capacity to adjust to the demands of their work. Using a complete sampling technique, nine employees made up the sample for this study. Questionnaires containing measures of perceived organizational support, career adaptability, and subjective career success factors that have been validated and re-tested were distributed in order to collect data. The study's findings suggest that subjective career success is positively and significantly impacted by perceived organizational support. Furthermore, career adaptability has a good and large impact on subjective career success, and perceived organizational support has a favorable and significant impact on career adaptability as well. Additionally, the mediation test results demonstrate that the relationship between perceived organizational support and subjective career success might be considerably mediated by career adaptability.